Complete chemical structures of human mitochondrial tRNAs - Takeo Suzuki (Nature Portfolio, 2020)
Mitochondrial tRNA modifications are important for tRNA stability and accurate decoding. By employing RNA mass spectrometry and deep sequencing, here the authors provide a comprehensive analysis of post-transcriptional modifications of 22 species of human mitochondrial tRNAs.